RETRACTED: NFIC suppressed the development of Glioma via modulating the balance of SHP2/PI3K and NF-κB/PTEN Signaling - Hongen Bao; Kai Liu; Naikang Gao; Youle Su; Huiru Bai; Changwu Dou; Fenjun Jiang; Fei Wang (PLoS ONE, 2026)
Objective The objective of this study is to elucidate the mechanism by which NFIC exerts its regulatory influence over NF-κB/PTEN, with a view to gaining insight into the processes underlying the proliferation and invasion of glioma cells. Methods The interactions between genes in gliomas were predicted and verified through bioinformatics analysis. The effect of NFIC on glioma development was detected via subcutaneous transplantation in nude mice. Protein expression levels of NFIC, OGN, NF-κB, SHP2, p-SHP2, PI3K, AKT, Cyclin A1, Cyclin D1, MMP-3, and MMP-9 were detected by western blot. The examination of tumour cell proliferation and invasion was conducted using the following assays: CCK-8, colony formation, scratch assay, Co-immunoprecipitation (Co-IP) experiment, Immunohistochemistry (IHC) experiment and Transwell. Results NFIC binds to the promoter regions of OGN and PTEN and regulates their transcription, leading to increased expression of these two genes,while simultaneously limiting the expression of NF-κB, SHP2, p-SHP2, PI3K, AKT, Cyclin A1, Cyclin D1, MMP-3, and MMP-9. NF-κB promotes SHP2 expression, whereas OGN and PTEN inhibit p-SHP2 expression. NFIC inhibits the proliferation and invasion of glioma cells, while NF-κB promotes these processes. Conclusion The overexpression of NFIC has the capacity to inhibit the PI3K/AKT signalling pathway, a process facilitated by the promotion of the expression of OGN and PTEN. This, consequently, results in the inhibition of glioma proliferation and development.